2019
DOI: 10.1038/s41467-019-13761-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of prefrontal cortex in the control of feature attention in area V4

Abstract: When searching for an object in a cluttered scene, we can use our memory of the target object features to guide our search, and the responses of neurons in multiple cortical visual areas are enhanced when their receptive field contains a stimulus sharing target object features. Here we tested the role of the ventral prearcuate region (VPA) of prefrontal cortex in the control of feature attention in cortical visual area V4. VPA was unilaterally inactivated in monkeys performing a free-viewing visual search for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 67 publications
6
77
0
Order By: Relevance
“…Our results are consistent with a single shared computational mechanism of attention implemented by a different neural architecture depending on the feature (Cohen & Maunsell, 2011). This view is supported by the similarity of neural effects for different forms of attention (Cohen & Maunsell, 2011;Treue & Martinez-Trujillo, 1999;Patzwahl & Treue, 2009;Ling, Jehee, & Pestilli, 2015;Jehee et al, 2011;Martinez-Trujillo & Treue, 2004), the additive or multiplicative advantage of combining multiple cues (Hayden & Gallant, 2009;White et al, 2015;Andersen et al, 2011;Goddard et al, 2019), and the similar top-down sources in prefrontal cortex from which attention signals are thought to originate (Corbetta & Shulman, 2002;Moore & Armstrong, 2003;Zhou & Desimone, 2011;Bichot, Xu, Ghadooshahy, Williams, & Desimone, 2019;Liu & Hou, 2013). From this perspective, spatial location is just another feature and spatial attention is a special form of feature-based attention (Treue & Martinez-Trujillo, 1999).…”
supporting
confidence: 84%
“…Our results are consistent with a single shared computational mechanism of attention implemented by a different neural architecture depending on the feature (Cohen & Maunsell, 2011). This view is supported by the similarity of neural effects for different forms of attention (Cohen & Maunsell, 2011;Treue & Martinez-Trujillo, 1999;Patzwahl & Treue, 2009;Ling, Jehee, & Pestilli, 2015;Jehee et al, 2011;Martinez-Trujillo & Treue, 2004), the additive or multiplicative advantage of combining multiple cues (Hayden & Gallant, 2009;White et al, 2015;Andersen et al, 2011;Goddard et al, 2019), and the similar top-down sources in prefrontal cortex from which attention signals are thought to originate (Corbetta & Shulman, 2002;Moore & Armstrong, 2003;Zhou & Desimone, 2011;Bichot, Xu, Ghadooshahy, Williams, & Desimone, 2019;Liu & Hou, 2013). From this perspective, spatial location is just another feature and spatial attention is a special form of feature-based attention (Treue & Martinez-Trujillo, 1999).…”
supporting
confidence: 84%
“…1 in Schall, 2015). In the studies by Bichot et al (2015, 2019), the authors identified a ventral prearcuate region (VPA) that was proposed as the human IFJ homologue and that overlapped with areas 46v, 45A and 12. Based on their injection sites, three regions that may correspond to the VPA were highlighted on the Yerkes19 atlas (b) (the regions 45A, 9/46v and 12r′ from the composite PFC parcellation by Donahue et al, 2018; PS, principal sulcus; AS, arcuate sulcus; both (a) and (b) were adapted from the datasets available in BALSA at https://balsa.wustl.edu/; Van Essen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In target search, the comparison is between objects in the display and a target representation; in popout search, the comparison is between objects in the display and one another. In both cases, the representations depend on ventral-stream visual areas like V4 and IT (Zhou & Desimone, 2011;Westerberg, Maier, & Schall, 2020) as well as prefrontal areas (Bichot et al, 2015;Bichot, Xu, Ghadooshahy, Williams, & Desimone, 2019). The processing involved in popout is likely related to the identification-based feedforward inhibition we already identified as important for target selection.…”
Section: Extensionsmentioning
confidence: 88%